HybridSPE: A novel technique to reduce phospholipid-based matrix effect in LC-ESI-MS Bioanalysis - Shafeeque Ahmad; Harsh Kalra; Amit Gupta; Bharat Raut; Arshad Hussain; Md Akhlaquer Rahman (Wolters Kluwer Medknow Publications, 2012)
When complex biological materials are analyzed without an adequate sample preparation technique, MS signal and response undergo significant alteration and result in poor quantification and assay. This problem generally takes place due to the presence of several endogenous materials component in samples. One of the major causes of ion suppression in bioanalysis is the presence of phospholipids during LC-MS analysis. The phospholipid-based matrix effect was investigated with a commercially available electro spray ionization (ESI) source coupled with a triple quadrupole mass spectrometer. HybridSPE dramatically reduced the levels of residual phospholipids in biological samples, leading to significant reduction in matrix effects. This new procedure that combines the simplicity of precipitation with the selectivity of SPE allows obtaining much cleaner extracts than with conventional procedures. HybridSPE-precipitation procedure provides significant improvement in bioanalysis and a practical and fast way to ensure the avoidance of phospholipids-based matrix effects. The present review outlines the HybridSPE technique to minimize phospholipids-based matrix effects on LC-ESI-MS bioanalysis.